2017
DOI: 10.1002/jso.24710
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of surgical quality for retroperitoneal sarcoma: Volume matters

Abstract: High-volume hospitals are significantly associated with surgery use and improved surgical outcomes. Consideration should be given to further centralization of RPS care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 27 publications
(53 reference statements)
2
36
0
Order By: Relevance
“…Moreover, this hypothesis is consistent with findings for other cancers showing lower operative mortality rates when surgeries are performed in hospitals with specialty expertise . Two recent studies using large cohorts from the National Cancer Data Base, one by Maurice et al and another by Keung et al published in this issue of Cancer , conclude that there is evidence to support a volume‐outcome association for patients with retroperitoneal sarcoma. Maurice et al go further and suggest regionalization of retroperitoneal sarcoma care to high‐volume centers.…”
Section: Examples From Panageas Et Al Illustrating Differences In Ressupporting
confidence: 79%
See 2 more Smart Citations
“…Moreover, this hypothesis is consistent with findings for other cancers showing lower operative mortality rates when surgeries are performed in hospitals with specialty expertise . Two recent studies using large cohorts from the National Cancer Data Base, one by Maurice et al and another by Keung et al published in this issue of Cancer , conclude that there is evidence to support a volume‐outcome association for patients with retroperitoneal sarcoma. Maurice et al go further and suggest regionalization of retroperitoneal sarcoma care to high‐volume centers.…”
Section: Examples From Panageas Et Al Illustrating Differences In Ressupporting
confidence: 79%
“…Two recent studies using large cohorts from the National Cancer Data Base, one by Maurice et al and another by Keung et al published in this issue of Cancer , conclude that there is evidence to support a volume‐outcome association for patients with retroperitoneal sarcoma. Maurice et al go further and suggest regionalization of retroperitoneal sarcoma care to high‐volume centers. These authors have obtained unique databases to address this important hypothesis.…”
Section: Examples From Panageas Et Al Illustrating Differences In Resmentioning
confidence: 99%
See 1 more Smart Citation
“…Also using the NCDB, Maurice et al reported outcomes among 3141 patients with RPS. However, approximately 30% of patients in this study did not undergo surgical resection and an HVH was defined as a hospital performing at least 5 surgical resections per year . Although RPS treatment at HVHs in this study was associated with higher rates of surgical resection and R0/R1 surgical resection, the authors did not find a survival difference between patients treated at HVHs and those treated at LVHs …”
Section: Discussionmentioning
confidence: 76%
“…To our knowledge, the current study is the first to investigate the impact of hospital volume on outcomes among patients undergoing surgical resection for RPS. Although 2 prior studies examined hospital volume and outcomes in patients with sarcoma, these studies were limited for several reasons . Gutierrez et al reported outcomes among 4205 patients with STS who were undergoing surgical resection, and demonstrated lower 30‐day and 90‐day mortality in patients treated at HVHs .…”
Section: Discussionmentioning
confidence: 99%